Pastern dermatitis outbreak associated with toxigenic and non-toxigenic Corynebacterium diphtheriae and non-toxigenic Corynebacterium ulcerans at a horse stable in Finland, 2021 - Grönthal TSC; Lehto AK; Aarnio SS; Eskola EK; Aimo-Koivisto EM; Karlsson T; Koskinen HI; Barkoff AM; He Q; Lienemann T; Rimhanen-Finne R; Mykkänen A (Germany, 2025)
Aims: Corynebacterium diphtheriae and Corynebacterium ulcerans, when producing toxin, are the cause of diphtheria, a potentially life-threatening illness in humans. Horses (Equus ferus caballus) are known to be susceptible to infection that may manifest clinically on rare occasions. In late 2021 and early 2022, specimens from five horses suffering from pastern dermatitis were cultured at the Laboratory of Clinical Microbiology at the Faculty of Veterinary Medicine, University of Helsinki, Finland. C. diphtheriae and/or C. ulcerans were recovered from all of these. This study aimed to (1) analyse the bacterial isolates and (2) describe the outbreak and identify possible sources of the infection and infection routes in the stable.
Methods and results: Susceptibility testing, PCR for the tox gene, and Elek test for toxin production in PCR-positive isolates were performed. Whole genome sequencing was also conducted to achieve high-resolution strain typing. An epidemiological survey was done by means of a semi-structured interview of horses' caretaker, and contact tracing was done among people at the stable. Two tox gene-positive, toxin-producing C. diphtheriae belonged to sequence type (ST) 822. Other C. diphtheriae (n = 2, ST828) and C. ulcerans (n = 2, ST325 and ST838) isolates did not carry the tox gene. The epidemiological investigation explored numerous possible routes of transmission, but the definite source of infection was not identified. All established human contacts tested negative for diphtheriae. All horses recovered after antimicrobial treatment.
Conclusions: Our study shows that C. diphtheriae and C. ulcerans may readily spread among horses at the same stable and complicate pastern dermatitis infections. These potentially zoonotic bacteria can cause outbreaks even in a country with a very low prevalence. Caretakers should be encouraged to wear gloves and practice good hand hygiene when treating infected skin lesions in horses.